Mapping and Ablation of Isolated Frequent Symptomatic Premature Atrial Contractions in Patients With Structurally Normal Heart - He, Bo; Li, Yi; Huang, Weiping; Yu, Wenxi; Zhao, Fang; Wu, Xiaoyan; Yao, Shuyuan; Po, Sunny S.; Lu, Zhibing (Frontiers in Cardiovascular Medicine, 2022)
Background: The present study investigated the safety and efficacy of mapping and ablating isolated premature atrial contractions (PACs) in patients with a structurally normal heart as well as whether PACs elimination by radiofrequency catheter ablation (RFCA) improved symptoms and the quality of life. Methods: Forty-three consecutive patients with frequent, symptomatic and drug-refractory PACs, but without atrial tachyarrhythmias (≥5 beats) were enrolled. In all patients, we performed physical, laboratory and imaging examinations to exclude structural heart disease. The quality of life questionnaire SF-36 before and 3 months after RFCA was performed in each patient. Results: Twenty-three men and 20 female with an average age of 52.6±17.6 years were finally enrolled. The mean number of PACs was 21685±9596 per 24 hours and the mean PACs burden was 28.9±13.7%. Short runs of tachycardia (<5 atrial beats) was observed in 32 patients (74.4%). All patients underwent successful RFCA without complication. The activation time at the successful ablation sites preceded the onset of the P-wave by 36±7.6 ms. During 15±8 months of follow-up, the recurrence of PACs was observed in 2 patients. The 24-hour PAC burden was significantly reduced 3 months after RFCA (mean 0.5%, P<0.05). The quality of life scores were significantly increased 3 months after RFCA (all P<0.05). Conclusions: RFCA was feasible, safe and effective to eliminate isolated frequent, symptomatic and drug-refractory PACs in patients with structurally normal heart. PACs elimination by RFCA significantly improved symptoms and the quality of life.